2017
DOI: 10.1111/eva.12561
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin‐mediated response to hyper‐thermal stress in the keystone speciesDaphnia magna

Abstract: Anthropogenic global warming has become a major geological and environmental force driving drastic changes in natural ecosystems. Due to the high thermal conductivity of water and the effects of temperature on metabolic processes, freshwater ecosystems are among the most impacted by these changes. The ability to tolerate changes in temperature may determine species long‐term survival and fitness. Therefore, it is critical to identify coping mechanisms to thermal and hyper‐thermal stress in aquatic organisms. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…This approach reconstructs microevolution by comparing within a population the phenotypes of organisms hatched from ancestral eggs with those from descendants hatched from more recent eggs (Orsini et al., 2013). Resurrection ecology has been successfully applied to document evolutionary responses of natural populations to warming (e.g., Cuenca Cambronero, Zeis, & Orsini, 2018; Geerts et al., 2015) and to contaminants (e.g., Kuester, Wilson, Chang, & Baucom, 2016; Turko et al., 2016). In contrast, this approach has been used only rarely to investigate the consequences of evolution in response to one stressor for a population's ability to deal with a second stressor (but see Zhang, Jansen, De Meester, & Stoks, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This approach reconstructs microevolution by comparing within a population the phenotypes of organisms hatched from ancestral eggs with those from descendants hatched from more recent eggs (Orsini et al., 2013). Resurrection ecology has been successfully applied to document evolutionary responses of natural populations to warming (e.g., Cuenca Cambronero, Zeis, & Orsini, 2018; Geerts et al., 2015) and to contaminants (e.g., Kuester, Wilson, Chang, & Baucom, 2016; Turko et al., 2016). In contrast, this approach has been used only rarely to investigate the consequences of evolution in response to one stressor for a population's ability to deal with a second stressor (but see Zhang, Jansen, De Meester, & Stoks, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…T imm is a thermal endpoint defined by the time taken for the loss of locomotory function to occur at constant, lethal temperature (Terblanche et al, 2011). While such acute measurements of thermal tolerance employ temperatures that do not directly reflect natural conditions, they are becoming a widely used relatively high-throughput tool for measuring among individual performance at high temperature (Cambronero et al, 2017;Manenti et al, 2014;Yampolsky et al, 2014) that have been shown to correlate with variables that describe distribution patterns (Clusella-Trullas, Blackburn, & Chown, 2011;Kellermann et al, 2012) and likely reflect the relative thermal tolerance of individuals experiencing chronic, suboptimal temperatures in the natural environment (Messmer et al, 2017). T imm was estimated using a custom algorithm in the r computing environment that can objectively identify the loss of locomotory function from video-derived tracking data (Burton, Zeis, & Einum, 2018).…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…In this context, one trait that has been of particular interest is the shortterm ability to tolerate high temperature (Brans et al, 2017;Manenti et al, 2014;Phillips et al, 2016;Yampolsky et al, 2014). Both static and dynamic measures of heat tolerance can show a clear acclimation response to mean temperature, whereby an increase in mean temperature triggers physiological responses that improve tolerance of acute high temperature events, with the effect of acclimation becoming more apparent at less acute temperature exposures (Cambronero, Zeis, & Orsini, 2017;Gunderson & Stillman, 2015;Semsar-kazerouni & Verberk, 2018;Shah, Ghalambor, & Funk, 2017). Moreover, a recent experiment revealed consistent differences in heat tolerance among three permutations of a stochastic thermal regime that had the same overall mean and variance but where the temporal predictability of fluctuations differed (Drake et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This involves resuscitation of ancestral populations from either natural populations (e.g., collected from sediment cores) or archived populations (e.g., seed bank collections) and then comparing these ancestral lineages to modern‐day descendants. Many of the contributions to this special issue take a “back‐in‐time” approach and focus on specific model organisms (e.g., Artemia —Lenormand et al., ; bacteria—Houwenhuyse, Macke, Reyserhove, Bulteel, & Decaestecker, ; Shoemaker & Lennon, ; Daphnia —Goitom et al., ; Cuenca Cambronero, Bettina, & Orsini, ; phytoplankton—Ellegaard, Godhe, & Riberio, ). However, as pointed out in the contribution from Franks et al., ; this issue), a “forward‐in‐time” approach (a.k.a.…”
Section: Resurrection Ecology (Re) Approachesmentioning
confidence: 99%
“…Other applied aspects of RE that are represented by contributions to this special issue, and that are important in understanding the ecology and evolution of natural populations and communities include (i) invasive species biology (i.e., Artemia —Lenormand et al., ); (ii) the role of RE in possible pathogen–host interactions that impact both human and nonhuman populations via “dispersal from the past” (i.e., melting permafrost releasing microbial pathogens—Houwenhuyse et al., ); (iii) climate and land‐use changes impacting nutrient enrichment (i.e., eutrophication of aquatic systems—Ellegaard et al., ; Cuenca Cambronero et al., ); and (iv) evolutionary feedback and ecosystem functioning (i.e., Goitom et al., ).…”
Section: Applied Evolutionary Aspects Of Re: Prospects and Limitationsmentioning
confidence: 99%